The Control of Permits for Selling Alcoholic Drinks in Medan City in Accordance with Medan Mayor Regulation Number 12 of 2011 - Muhammad Rizal (RIRAI Publisher, 2022)
Mayor Regulation is a type of statutory regulation set by the mayor. However, the new Mayor's Regulations are recognized and have binding legal force as long as they are ordered by higher laws and regulations or are formed based on authority. Regulation of the Mayor of Medan Number 12 of 2011 concerning levies for permits for selling alcoholic beverages Medan City. The reason for this research is that the researcher wants to know the control of permits for selling alcoholic beverages Medan City in accordance with the Regulation of the Mayor of Medan Number 12 of 2011. This study uses the approach method used in this study is a qualitative approach which is used to describe and analyze the phenomenon. , events, social activities, attitudes, beliefs, perceptions and people individually or in groups. And the results of the study indicate that the control of permits for selling alcoholic beverages in Medan City in accordance with the Regulation of the Mayor of Medan Number 12 of 2011 has not been implemented properly and properly. This is because there are still many sellers of alcoholic beverages who do not have an official business license